Analysis of Students Critical Thinking Skills in Nervous System Learning Based on the Level of School Favoritism in Sleman Regency - Wulandari*, Novia Dian Kartika; Kuswandi, Paramita Cahyaningrum; Khan, Farwa Hafeez (Jurnal Pendidikan Sains Indonesia, 2024)
Critical thinking skills (CTS) are importante cognitive ability to be improved by students in solving problems in the future. This ability needs to be trained in learning at school to equip students in the 21st century. Problems with students' CTS can lead to a decrease in the quality of education and the quality of students. The purpose of this study was to analyze the profile of CTS of high school students at Sleman Regency in biology learning, especially on the topic of the nervous system. This type of research is descriptive research. The research was conducted in six high schools throughout Sleman Regency. The population in this study is grade XI students in six high schools consisting of two most favorite category schools, two favorite category schools, and two less favorite category schools in Sleman Regency. Sampling using random purposive sampling method from six high schools in Sleman Regency totaling 216 students. The data collection technique using the question test method is using test instrument sheet. The data analysis technique used quantitative descriptive. The results showed that the CTS of high school students at Sleman Regency in biology learning reached an average of 46.6% in the medium category. Schools with most favorite categories have the highest CTS for all aspects tested compared to favorite and less favorite category schools. Meanwhile, the lowest CTS is the less favorite category of schools. This shows that schools with most favorite categories have better CTS for all aspects